Characterization of multiple constituents in rat plasma after oral administration of Shengmai San using ultra-performance liquid chromatography coupled with electrospray ionization/quadrupole-time-of-flight high-definition mass spectrometry. Issue 3 (7th February 2015) - Han, Ying; Wu, Fangfang; Zhang, Aihua; Sun, Hui; Wei, Wenfeng; Wang, Xijun
<x xml:space="preserve">Abstract</x> A rapid and robust UPLC-Q-TOF-HDMS approach has been applied for the online identification of multiple components in rat plasma after the oral administration of SMS.